从文图学的角度看泰剧《以你的心诠释我的爱》= A study of the Thailand TV series "I told sunset about you" from the perspective of text and image studies - Lim, Ebel Jia En (Nanyang Technological University, 2021)
2020下半年在泰国播出了一部掀起一阵热潮的耽美剧《以你的心诠释我的爱》（以下简称《以爱》），该剧主要讲了两位男孩子的青春爱情故事以及家庭生活。这部剧的拍摄地点主要在泰国的普吉岛并且蕴含了丰富的中国文化元素，故事结合了中国传统文化使这部剧的剧情结构和人物色彩更加多元化。 这部剧之所以被很多人称之为“永远的神”（意思是非常的经典），是因为它与其他的泰国耽美剧的相比，不同在于这部剧是改编了两位男孩自己现实生活中的故事而并非是改编纯虚构的耽美小说。由于两位主演在开拍之前是已经关系密切的好友，并互相陪伴多年，因此能够让观众把自己代入角色中去体验，为整部剧添加了更多的真实性。在剧播出后，以爱迅速在中国以及泰国掀起了一波热潮。而这也让两位主演因为这部剧的种种美好瞬间在泰国以及中国爆红。无论是剧情的处理，真人CP的时间线和不同的文化色彩，还是由剧衍生的周边商品设计，这些都是促使了这部剧成功的重要因素。 本文希望以通过文图学的角度来分析《以爱》这部作品并深度剖析故事背景以及其成功的原因。 关键词：《以你的心诠释我的爱》、文图学、电视剧、耽美、泰剧 In the later half of the 2020, I told Sunset About You ( ITSAY ) was aired in Thailand. This coming of age drama mainly described the growth of the two boys. The drama is filmed in Phuket, Thailand and it has China culture elements in it. This drama is being well loved by many. The reason why this drama stands out from the other drama is because this drama is actually adapted from the real life story of the two main leads. The two main leads were friends way before this drama and hence many audiences look forward to seeing their story in the drama. After it was aired, the drama became a hot topic in Thailand and China. Hence, this resulted in both the main leads raise to fame. The CP timeline, details of the drama and the design of the merchandises are the reasons why this drama became successful. This essay would like use the text and image studies to analyse the reason of the success. Keywords: I Told Sunset About You, Text and Image Studies, Television Drama, Boys’Love, TV series of Thailand